Analysis of the wireless communication latency and its dependency on a data size - Horálek, Josef; Svoboda, Tomáš; Holík, Filip (IEEE (Institute of Electrical and Electronics Engineers), 2016)
Aim of this article is to introduce the results of measurement of latency in wireless networks and its dependency on the size of the sent data. Latency and its role in wireless networks are described in detail. Based on the theoretical background, three experimental topologies were designed. These topologies are used to measure latency in wireless networks. The rate of latency, depending on the size of outgoing data is based on test results. This article also presents the prediction when the packet size may be determined so that it is possible to minimize interdependence of latency and data sent and to reduce the latency.
Analýza latence bezdrátové komunikace a její závislosti na velikosti dat
Keywords: Latency; measurement; data size; wireless network; Latence; měření; velikost dat; bezdrátová síť